Prevention of tuberculosis among HIV-infected patients - Z. M. Zagdyn (Туберкулез и болезни лёгких)
The advances that have been made in the wide use of antiretroviral therapy in the past decade, which increase longevity and improve quality of life in treated patients with HIV infection are waning because of the high prevalence of tuberculosis among this population. According to the World Health Organization estimates, among 8.6 million tuberculosis patients globally in 2012, there were 1.1 million HIV-seropositive people, of them 320,000 died from different causes. In the Russian Federation, 29,708 patents were co-infected with tuberculosis and HIV in 2012, of them 5,292 died, including 1,152 persons from tuberculosis. HIV-seropositive persons fall ill with tuberculosis 20-30 times more frequently than HIV-negative ones. Consequently, the prevention of tuberculosis becomes the most important area in reducing its burden among the people living with HIV infection, particularly in the countries where these two infections are common. The purpose of this publication is to review the existing guidelines and the investigations conducted in different countries, including in Russia, to study the preventive use of antituberculosis drugs to reduce tuberculosis morbidity and mortality among the HIV-seropositive population.